Datos meteorológicos de la Estación Gonnet del LAyHS (FAU-UNLP) correspondientes al año 2008 - Czajkowski, Jorge Daniel (2009)
Datos meteorológicos de la Estación Gonnet del LAyHS (FAU-UNLP) correspondientes al año 2008.